Microstructure of Electrodeposited Cu Micro-cylinders in High-Aspect-Ratio Blind Holes and Crystallographic Texture of the Cu Overburden Film. Issue 4 (April 2016) - Zhang, Yazhou; Ding, Guifu; Wang, Hong; Cheng, Ping
Abstract : Microstructure and texture of electrodeposited Cu micro-cylinders in the blind hole play a vitally important role in the electrical and mechanical properties of the three-dimensional (3-D) IC (integrated circuit)/Si integrations. In this paper, a new commercial additive system, which is specifically developed for the high-aspect-ratio through-silicon-via (TSV) filling, was used to electrodeposit Cu in the blind holes. The microstructure of electrodeposited Cu micro-cylinder in the blind hole with a diameter of 40 µm and a depth of 140 µm was investigated by electron back-scattered diffraction (EBSD) technique. Grain size distribution of the Cu micro-cylinder in the blind hole differed from the bottom to the top. The grain boundaries contained a high fraction of Σ3 CSL (coincident site lattice) boundaries. It has been reported that the Cu overburden film on the surface of the blind hole influenced the crystallographic orientation of Cu grains inside the damascene trench. So the effects of the current density and additive concentration on the crystal structure of the overburden Cu film were also studied in this study. The experimental results indicated that the preferred orientation of the Cu overburden film changed from 111 to 220 when the current density increased from 2 to 80 mA cm −2 . However, the effect of additives on the crystal structure of the Cu overburden film was dependent on the crystal structure of the seed layer.